Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Intrinsik Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Mediasi: Studi pada Pegawai Kantor Sekretariat Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Halmahera Timur - Muhiddin Ahad; Abdul Rahman Jannang; Marwan Man Soleman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to assess the impact of transformational leadership style and intrinsic motivation on employee performance through job satisfaction at the Secretariat of the Regional People's Representative Council (DPRD) of East Halmahera Regency. The total sample in this study consisted of 60 employees at the Secretariat of the Regional People's Representative Council (DPRD) of East Halmahera Regency. The sample selection method used was Structural Equation Modeling (SEM). The analytical test tool used was path analysis using the Partial Least Square (PLS) program. The results of the study show: Transformational Leadership Style on Employee Performance has a positive and significant effect, Intrinsic Motivation on Employee Performance has a positive and significant effect, Transformational Leadership Style on Job Satisfaction has a positive and significant effect, Intrinsic Motivation on Job Satisfaction does not have a positive and significant effect, Job Satisfaction on Employee Performance has a positive and significant effect, Transformational Leadership Style on Employee Performance in Mediation by Job Satisfaction has an influential and significant effect, Intrinsic Motivation on Employee Performance in Mediation by Job Satisfaction has no significant effect.